Implementación de la contabilidad comercial e indicadores financieros en Ultranet, de la ciudad de Catamayo, provincia de Loja, periodo noviembre a diciembre/2015 - Carrión Torres, Nataly Adriana (2017)
This thesis developed with the aim of providing information relating to the economic and financial activity of the target company study, obtain information that allowed the registration of economic movements - by applying financial accounting principles and standards in order to provide data of economic events that occurred in the company in continuous, orderly and systematic way. Through the implementation of commercial accounting ULTRA NET, the canton Catamayo, period November to December 2015, the financial situation of the company was known, through procedures that began with the lifting of inventory, general ledger, auxiliary sales in which corresponding to Internet services and sales of various products is reflected values; becoming valid instruments to perform the accounting process and presentation of financial statements that reflect the corporate financial situation. At the end of the investigative work we present conclusions and recommendations aimed primarily those organized way to continue with the implementation of accounting for the activity performed by the company, in this way we achieve real information in a timely fashion; compliance with tax obligations and avoiding unnecessary costly glosses.